PARTISPATORY DEVELOPMENT COMMUNICATION: OPTIMALISASI PERAN PEREMPUAN DALAM PROGRAM PEMBERDAYAAN PEREMPUAN DPMGP4 KABUPATEN NAGAN RAYA - Reni Juliani; Putri Maulina; Desi Maulida (Universitas Riau Kepulauan, 2023)
ABSTRACTWomen have the ability to play a role as strategic actors in Indonesia's development, as well as women from Nagan Raya District. The purpose of this research is to dig deeper into optimizing the role of women in women's empowerment programs in partnership with the Office of Community Empowerment, Gampong, Population Control and Women's Empowerment (DPMGP4).A qualitative approach is the method of this research with informants coming from the person in charge of Sikula Geutanyoe program, which is a Student Organization Capacity Building Program for the State Administration Student Association (PPK ORMAWA HIMADISTRA) at Teuku Umar University in collaboration with DPMGP4. Data was collected by means of interviews, observation and documentation. Determination of informants with purposive sampling technique and totaling 5 people came from the person in charge of the Sikula Geutanyoe Program 3 informants and from DPMGP4 2 informants. The data that has been obtained is then analyzed through 3 stages, the first is selecting data, then presenting the data and the last step is making conclusions. The results of the research show that optimizing the role of women has been carried out through the